Policy on Empowering Women Victims of Violence: A Case Study at the Office of Women's Empowerment, Child Protection, and Population - Iga Wahyudi Firmansyah; Kridawati Sadhana; Roos Widjajani (Innovation Business Management and Accounting Journal, 2025)
This study aims to describe and analyze the implementation of policies to empower women victims of violence and identify supporting and inhibiting factors in implementing these policies. The research was conducted at the East Java Province Office of Women's Empowerment, Child Protection, and Population (DP3AK). The data collection techniques used were observation, interviews, and documentation. The data analysis technique in this study uses qualitative data analysis with the stages of data collection, data reduction, data presentation, and conclusions. The research findings show that the implementation of policies to empower women victims of violence in DP3AK East Java Province is carried out through the stages of assessment, planning, monitoring, implementation, and evaluation. A participatory approach is applied, but there are still challenges in coordination with districts/cities and participant selection. Supporting factors include collaboration, policy support, resources, and SIMFONI PPA. Barriers included superficial monitoring, less open coordination, budget limitations, and community stigma that affected the effectiveness of the training. The results of the study are expected to contribute to the DP3AK of East Java Province, especially in the Field of Women's Protection and Family Quality, as well as other government agencies in Indonesia in the implementation of programs to empower women victims of violence, as well as a reference for similar studies.